Experimental Analysis of Power Quality in LED and CFL Lamps Under Cyclic Switching Regimes (Ciencias de la Ingeniería y Aplicadas, 2026)
This study experimentally evaluated the influence of different ON and OFF operating regimes on the power quality of LED and CFL lamps using a quantitative approach in a single phase 127 V, 60 Hz circuit. Six 80 W lamps per technology were connected in parallel and measurements were performed using a Class A Fluke 1775 power quality analyzer operating in compliance with IEC 61000 4 30, IEC 61000 4 7 and IEC 61000 4 15 measurement specifications. The parameters analyzed included voltage total harmonic distortion, third order harmonic content, long term flicker and the number of transient events. Four operating regimes were applied comprising a continuous twenty four hour test and three cyclic ON periods of 60, 30 and 10 min with 2 s OFF intervals. Results indicated that both harmonic distortion and event count increased as switching frequency rose, with LED lamps exhibiting the most pronounced variation. Under continuous operation CFL lamps presented the highest flicker level while LED lamps produced a greater impact under repetitive switching. These findings characterize the electrical behavior of both technologies in scenarios with varying switching patterns.
Keywords: Electric power quality; Lighting; Energy efficiency; Harmonics; Alternating current; Electrical equipment; Electrical disturbances